2011
DOI: 10.1186/1471-2458-11-107
|View full text |Cite
|
Sign up to set email alerts
|

Sickness absence in musculoskeletal disorders - patients' experiences of interactions with the Social Insurance Agency and health care. A qualitative study

Abstract: BackgroundSickness absence has represented a growing public health problem in many Western countries over the last decade. In Sweden disorders of the musculoskeletal system cause approximately one third of all sick leave. The Social Insurance Agency (SIA) and the health care system are important actors in handling the sickness absence process. The objective was to study how patients with personal experience of sickness absence due to musculoskeletal disorders perceived their contact with these actors and what … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(80 citation statements)
references
References 18 publications
(27 reference statements)
5
75
0
Order By: Relevance
“…The importance of providing work-related interventions and adaptation of work for sick-listed From a patient perspective, it appears that support and adjustment at the workplace is a facilitating prerequisite for RTW (19)(20)(21), and specific goals for each patient can benefit the RTW process (18,30,32). We found that adjustments to work tasks or the work environment were the most prevalent interventions at the workplace for both diagnostic groups.…”
Section: Work-related Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of providing work-related interventions and adaptation of work for sick-listed From a patient perspective, it appears that support and adjustment at the workplace is a facilitating prerequisite for RTW (19)(20)(21), and specific goals for each patient can benefit the RTW process (18,30,32). We found that adjustments to work tasks or the work environment were the most prevalent interventions at the workplace for both diagnostic groups.…”
Section: Work-related Interventionsmentioning
confidence: 99%
“…There is some evidence that collaboration between the sick-listed patient, health care providers and the employer favours the rehabilitation process (10,(16)(17)(18). Patients consider their contact with the health care provider as an important part of their rehabilitation that affects recovery and return to work (RTW) (17,(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…The worker is subject to the power imbalance with the system, prolonged claims and appeals processes, medical reports being used out of context, and a general lack of knowledge about rights. Claims can be manipulated by ignoring or contesting diagnoses, using confusing jargon and legalistic communication, slow payments to non-preferred physician to discourage treatment [86][87][88][89][90][91][92][93][94][95][96][97][98].…”
Section: Worker's Compensation Is Underutilizedmentioning
confidence: 99%
“…For example, a social insurance agent may focus on medico-legal conceptions of work ability while an employer is concerned about productivity and an employment agent may focus on employability on a competitive labour market while the patient is concerned about attending work, economic self-sufficiency and keeping a job despite periods of sick-leave [1,35,38]. If such perspectives are made explicit it is easier to help patients to interact optimally.…”
Section: Discussionmentioning
confidence: 99%